From support to engagement: how counseling and parental involvement influence students through grit and motivation - Fadilah, Haris; Ma'ruf, Hidayat; Jannah, Raihanatul; Rahmi, Nurul (Jurnal Konseling dan Pendidikan, 2025)
Student engagement plays a pivotal role in academic success. This study aims to examine the effects of counseling satisfaction (SAT), school climate (SC), Islamic religiosity (REL), and parental involvement (PI) on students’ grit and motivation (MOT), and to assess their indirect effects on SE through grit and MOT. The sample consisted of 338 (F = 214, M = 124) high school students from South Kalimantan, Indonesia, including 205 students from general high schools and 133 from Islamic high schools. The sample was selected using a convenience sampling technique.  The data analysis method used in this study was Partial Least Squares Structural Equation Modeling (PLS-SEM).  The findings indicated that all exogenous variables significantly influence grit and MOT, except for the non-significant effects of SAT on MOT and SC on grit. Grit and MOT significantly mediated the effects of exogenous variables on student engagement. However, grit did not mediate the impact of SC, and motivation did not mediate the effect of SAT. PI significantly enhances student grit, which in turn strongly predicts SE, highlighting its key mediating role. However, the sampling technique used may have introduced potential bias and limited the generalizability of our findings. These findings suggest that school counseling programs should also focus on enhancing parental awareness and involvement in their children's education.